Desarrollo de un libro interactivo basado en la obra Campiña Lojana del autor Dr. Gabriel Gonzalo Gómez Gómez para dispositivos móviles con sistema operativo android como fuente de consulta en el área de estudios sociales, para los alumnos de los cuartos grados de educación básica - Jaramillo Sánchez, Richard Augusto (2015)
In order to strengthen knowledge, is planting aims to develop an interactive book based on the author's work lojana countryside Dr. Gabriel Gonzalo Gómez Gómez for mobile devices with Android operating system. As a reference in the area of social studies for students in the fourth grade of primary education. To conduct this research work the ICONIX methodology was used, which allowed analyzing each of the requirements and interests of both students and faculty, as a basis for the design and implementation of application for Android phones. As a result an agile application was developed with the design of graphical interfaces that allow the application to be nice, easy to use, customizable and content that will support within the teaching-learning process itself and as a reference in the Department of Social Studies for its geographical and historical contents of the province of Loja. Thus he contributed a technological tool that allows teachers and students invigorate the teaching-learning process of the subject of Social Studies.